A fenntartható információs társadalom ideológiai tájképe. 1. rész (Sustainable Information Society as Ideology. First Part, in Hungarian) - Fuchs, Christian (Információs Társadalom (Information Society))

Some Theoretical Foundations of Critical Media Studies: reflections on Karl Marx and the media - Fuchs, Christian (International Journal of Communication 3 (2009))

The role of income inequality in a multivariate cross- national analysis of the digital divide - Fuchs, Christian (Social Science Computer Review)

Cyberethics and Co- operation in the Information Society - Fuchs, Christian; Bichler, Robert; Raffl, Celina (Science and Engineering Ethics)

A Contribution to Theoretical Foundations of Critical Media and Communication Studies - Fuchs, Christian (Javnost-The Public)

Internet und Gesellschaft: Beiträge zu einer kritischen Theorie des Informationszeitalters [Internet and Society: Contibutions to a Critical Theory of the Information Age] - Fuchs, Christian (Neue Medien und kulturelle Vielfalt [New Media and Cultural Diversity])

Grundlagen der Kritik der Politischen Ökonomie der Medien [Foundations of the critique of the political economy of the media] - Fuchs, Christian (Bruchstücke: Kritische Ansätze zu Politik und Ökonomie im globalisierten Kapitalismus)

Towards a Critical Theory of Information - Fuchs, Christian (tripleC (cognition, communication, co-operation): Journal for a Global Sustainable Information Society)

Autopoiesis and Critical Social Systems Theory - Fuchs, Christian; Hofkirchner, Wolfgang (Autopoiesis in Organization Theory and Practice)

Kapitalistische Medien und kapitalistische Krise [Capitalist media and capitalist crisis] - Fuchs, Christian (Kapitalismus am Ende? [The end of capitalism?])

Conference Report: The Internet as Playground and Factory (November 12-14, 2009, The New School, New York City, USA) - Fuchs, Christian (tripleC)

Ordered Mesoporous In2O3: Synthesis by Structure Replication and Application as a Methane Gas Sensor - Waitz, Thomas; Wagner, Thorsten; Sauerwald, Tilman; Kohl, Claus-Dieter; Tiemann, Michael (Advanced Functional Materials)
The synthesis and characterization of ordered mesoporous In2O3 materials by structure replication from hexagonal mesoporous SBA-15 silica and cubic KIT-6 silica is presented. Variation of the synthesis parameters allows for different pore sizes and pore wall thicknesses in the products. The In2O3 samples turn out to be stable up to temperatures between 450 °C and 650 °C; such high thermal stability is necessary for their application as gas sensors. Test measurements show a high sensitivity to methane gas in concentrations relevant for explosion prevention. The sensitivity is shown to be correlated not only with the surface-to-volume ratio, but also with the nanoscopic structural properties of the materials.

Time-resolved photoluminescence study of mesoporous ZnO nanostructures - Schwalm, Michael; Horst, Swantje; Chernikov, Alexej; Rühle, Wolfgang W.; Lautenschläger, Stephan; Klar, Peter J.; Meyer, Bruno K.; Waitz, Thomas; Tiemann, Michael; Chatterjee, Sangam (physica status solidi (c))
We report a systematic study of the photoluminescence properties of ZnO nanostructures. In particular, mesoporous ZnO powders of varying surface-to-mass ratio are investigated and compared to a bulk reference. At low temperatures the emission from higher-energy states is very pronounced and even dominant for samples with high surface-to-mass ratio.

Social Networking Sites and the Surveillance Society - Allmer, Thomas; Sandoval, Marisol (American Philosophical Association Newsletter on Philosophy and Computers)

Morals in the world-picture - Matzner, Tobias (Sprache und Welt: Beiträge des 32. Internationalen Wittgenstein Symposiums)

Learning Parametrised RoboCup Rescue Agent Behaviour Using an Evolutionary Algorithm - Kruse, Michael; Baumann, Michael; Knieper, Tobias; Seipel, Christoph; Khaluf, Lial; Lehmann, Nico; Lermontow, Alex; Messinger, Christian; Richter, Simon; Schmidt, Thomas; Swars, Daniel

Coupling Dynamics of Quantum Dots in a Liquid-Crystal-Tunable Microdisk Resonator - Förstner, Jens; Meier, Cedrik; Piegdon, Karoline; Declair, Stefan; Hoischen, Andreas; Urbanski, Mark; Meier, Torsten; Kitzerow, Heinz-Siegfried (Advances in Optical Sciences Congress)
We experimentally and theoretically investigate microdisk resonators with embedded quantum dots immersed in a liquid crystal in its nematic phase, showing the tunabililty of the photonic modes via external parameters like temperature or electric field.
Keywords: tet_topic_microdisk

Konsumgesellschaft - Kleinschmidt, Christian (Sic et Non. Zeitschrift Philosophie / Kultur im Netz)

Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten

Schäfer, Friedrich August (1883-1958) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Foerster, Gotthilf Helmut (1895-1964) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Lehmbruck, Wilhelm (1881-1919) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Sehlbach, Erich (1898-1985) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Weigle, Maria (1893-1979) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Bunk, Gerard (1888-1958) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Heyne, Bodo (1893-1980) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Peters, Ilse - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Biblische Bilder - Beobachtungen zur Transformation der Bibel in der Klaviermusik in Deutschland im 19. und 20. Jahrhundert - Schroeter-Wittke, Harald (Inszenierungen der Heiligen Schrift. Jüdische und christliche Bibeltransformationen vom Mittelalter bis in die Moderne)

Ruhrgebietsperikopenreihe. Wir werden aber alle verwandelt werden (1 Kor 15,51b). Mit der Bibel durch RUHR 2010. Eine Perikopenreihe für das Ruhrgebiet - Schroeter-Wittke, Harald (Wir werden aber alle verwandelt werden. Handreichung zu den "Local Hero Wochen" in der Kulturhauptstadt RUHR 2010)

Heilige Scheu und profane Hygiene. Abendmahl als Zeichen der Nähe - Zwischen Scham und Verbundenheit - Schroeter-Wittke, Harald (Näher! 7 Wochen ohne Scheu. Arbeitshilfe zum Thema "Näher!")

"Zur Recreation des Gemüths" - Musik als Seelsorge - Schroeter-Wittke, Harald (Seelsorge heute. Aktuelle Perspektiven aus Theorie und Praxis)

Hören - Theologische Hermeneutik populärer Hörwelten - Schroeter-Wittke, Harald (Sinnspiegel. Theologische Hermeneutik populärer Kultur)

Big Boss oder: Im Spiel üben wir Verlieren-Können. 10 zuversichtliche Mutmaßungen zum Brettspielen von Erwachsenen - Schroeter-Wittke, Harald (Erwachsen werden - Erwachsen sein)

Prophetie zwischen Zeitansage und Bibelgebrauch - Impulse der biblischen Prophetie für die Praxis der Christinnen und Christen heute - Schroeter-Wittke, Harald (Erziehen heute)

Popkultur und Religion - Best of...

Ultrafast Coherent Interactions in Quantum Wells Studied by Two-Dimensional Fourier Transform Spectroscopy - Meier, Torsten; Zhang, Tianhao; Kuznetsova, Irina; Yang, Lijun; Bristow, Alan D; Dai, Xingcan; Li, Xiaoqin; Thomas, P.; Mukamel, S.; Mirin, Richard P.; Cundiff, S.T. (Ultrafast Phenomena XVI: Proceedings of the 16th International Conference, Palazzo dei Congressi Stresa, Italy, June 9--13, 2008)

Generation and time‐resolved detection of coherently controlled electric currents at surfaces - Meier, Torsten; Güdde, Jens; Rohleder, M.; Koch, S.W.; Höfer, Ulrich (physica status solidi c)
We demonstrate a technique for the generation and detection of electron currents at surfaces on a femtosecond time scale with a contact-free experimental setup based on a combination of coherent control and photoemission spectroscopy. We have applied this technique for electrons excited into image-potential states on a Cu(100) surface that form a free-electron-like band in the direction parallel to the surface. The photogeneration of currents is described by optical Bloch equations for a multiband model. By incorporating field-induced interband and intersubband transitions together with intraband accelerations into the model, the observed phase dependence of the population and of the current can be reproduced.

Incremental forming of tubes and sheets assisted by friction-induced heating - Homberg, Werner; Hornjak, Daniel; Beerwald, Charlotte; Rostek, Tim; Kunert, Joachim; Wilk, D.

Information and Communication Technologies & Society: A Contribution to the Critique of the Political Economy of the Internet - Fuchs, Christian (European Journal of Communication)

A Contribution to the Critique of the Political Economy of Transnational Informational Capitalism - Fuchs, Christian (Rethinking Marxism)

Review of “The Problem of Order in the Global Age“ (Andreas Pickel) - Fuchs, Christian (tripleC)

A Contribution to Critical Globalization Studies. Centre for the Critical Study of Global Power and Politics Working Paper CSGP 09/8 - Fuchs, Christian

Gas sensor based on ordered mesoporous In2O3 - Wagner, T.; Sauerwald, T.; Kohl, C.-D.; Waitz, T.; Weidmann, C.; Tiemann, Michael (Thin Solid Films)
We present the preparation of a semiconductor gas sensor based on ordered mesoporous In2O3. The In2O3 was synthesized by structure replication procedure from cubic KIT-6 silica. A detailed analysis of the morphology of the mesoporous powders as well as of the prepared sensing layer will be shown. Unique properties arise from the synthesis method of structure replication such as well defined porosity in the mesoporous regime and nanocrystallites with high thermal stability up to 450 °C. These properties are useful for the application in semiconducting gas sensors. Test measurements show sensitivity to methane gas in concentrations relevant for explosion prevention.

Halbleitende Metalloxide als Gassensoren im Chemieunterricht - Waitz, Thomas; Tiemann, Michael (CHEMKON)
Halbleitende Metalloxid-Gassensoren werden sowohl im industriellen Bereich als auch im Haushalt zur Luftüberwachung verwendet. Die Funktionsweise basiert auf einer reversiblen Änderung des Sensorwiderstandes in Anwesenheit sowohl oxidierender als auch reduzierender Gase, die mit einfachen Mitteln gemessen werden kann. In diesem Artikel wird vorgestellt, wie sich die bei der Gasdetektion ablaufenden Vorgänge mit Hilfe des Ionosorptionsmodells in Kombination mit einem einfachen Festkörperbändermodell deuten lassen. Abschließend werden einfache, im Chemieunterricht zu realisierende Experimente mit Gassensoren präsentiert.

Autonomous Sensor Nodes for Aircraft Structural Health Monitoring - Becker, Thomas; Kluge, Martin; Schalk, Josef; Tiplady, Keith; Paget, Christophe; Hilleringmann, Ulrich; Otterpohl, Tobias (IEEE Sensors Journal)
Keywords: Electrical and Electronic Engineering; Instrumentation

Efficient Antenna Design of Inductive Coupled RFID-Systems with High Power Demand - Reinhold, Christian; Scholz, Peter; John, Werner; Hilleringmann, Ulrich (Journal of Communications)
Keywords: Electrical and Electronic Engineering

N-type single nanoparticle ZnO transistors processed at low temperature - Wolff, Karsten; Hilleringmann, Ulrich (2009 Proceedings of the European Solid State Device Research Conference)

Lock Detection for Charge-Pump Phase-Locked Loops - Wiegand, C; Hedayat, C; Hilleringmann, Ulrich (Sophia Antipolis Microelectronics SAME)

Finite symplectic matrix groups (Dissertation) - Kirschmer, Markus
Die invarianten Formen aus dem Anhang sind hier verfügbar:http://www.math.rwth-aachen.de/homes/Markus.Kirschmer/symplectic/

von der Leyen zu Bloemersheim, Friedrich Heinrich Freiherr (1769-1825) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

von Kotzebue, August Friedrich Ferdinand (1761-1819) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Möller, Anton Wilhelm Peter (1762-1846) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Meister, Christoph Georg Ludwig (1738-1811) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Summermann, Caspar Theodor (1674-1752) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Carstanjen, Conrad Jacob (1763-1840) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Jorissen, Matthias (1739-1823) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

von Holy, Gerhard (1677-1736) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Krummacher, Cornelius Friedrich Adolf (1824-1884) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Bisping, Maximilian Anton Wilhelm (1817-1890) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Krummacher, Gottfried Daniel (1774-1837) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Ettling, Georg Friedrich Ludwig (1873-1942) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Lahusen, Christoph Friedrich (1851-1927) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Hoesch, Karl Albert Alexander (1847-1898) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Krummacher, Emil Wilhelm (1798-1886) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Olimart, Franz (1869-1943) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Keßler, Gerda, geb. Bertram (1911-1983) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Brevier fürs Revier. Mit der Bibel durch RUHR.2010

Siemoneit, Hans Rudolf (1927-2009) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Hüsch, Hanns Dieter (1925-2005) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Rutenborn, Günter (1912-1976) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Bernds, Heinrich (1901-1945) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Paskert, Ruth (1910-2004) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Wir werden aber alle verwandelt werden. Handreichung zu den "Local Hero Wochen" in der Kulturhauptstadt RUHR 2010 - Mawick, Gudrun; von Melle, Sebastian; Reichlung, Philipp E.; Schroeter-Wittke, Harald

Die gegenwärtige Praxis des Abendmahls. Bedingungen - Herausforderungen - Perspektiven - Schroeter-Wittke, Harald (Praktische Theologie)

Multikulturelle Urgeschichte. Zur Genesis-Suite von 1945 aus Hollywood - Schroeter-Wittke, Harald (Praktische Theologie)

Four Biblical Dances. Zum 80. Geburtstag von Petr Eben - Schroeter-Wittke, Harald (Praktische Theologie)

Abendmahl

Ja, wo singen sie denn? - Schroeter-Wittke, Harald (Junge Kirche)

Die Propheten im Aufbau der Bibel - Schroeter-Wittke, Harald (Erziehen heute)

Silent Night - X-mas Jazz - Schroeter-Wittke, Harald (Praktische Theologie)

Kristian Fechtner: Im Rhythmus des Kirchenjahres. Vom Sinn der Feste und Zeiten, Gütersloh 2007 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Klaus Kirchhoff: das gewisse Etwas. Phänomenologische Ansätze der Religionspädagogik - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Andrea Bieler / Luise Schottroff: Das Abendmahl. Essen, um zu leben. Gütersloh 2007 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

13. Sonntag nach Trinitatis. Lk 10,25-37: Eine überfallartige Geschichte, oder: Lesen, als ob das Leben davon abhinge - Schroeter-Wittke, Harald; Kirsner, Ing (Predigtstudien I/2)

Invokavit. Lk 4,1-13: Die zarteste Versuchung, seit es Kohle gibt - Schroeter-Wittke, Harald (Brevier fürs Revier)

Sexagesimae. Hebr 4,12f: Lebendig und kräftig und schwerter - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Lauter Hoffnung - Hoffnung lauter. Ein vierstimmiger Akkord aus dem 1. Petrusbrief - Schroeter-Wittke, Harald (Krichentagssonntag 31. Januar 2010)

Mit Gott lässt sich nicht rechnen - aber spielen! - Schroeter-Wittke, Harald (Text-Raum)

7. Sonntag nach Trinitatis. Joh 6,1-15: Christliche Zeichensetzung, oder: Abendmahl mit Aussetzungsworten - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Anticrossing of Whispering Gallery Modes in Microdisk Resonators Embedded in a Liquid Crystal - Förstner, Jens; Declair, S.; Meier, Cedrik; Meier, Torsten (Theoretical and Computational Nanophotonics Tacona-Photonics)
We numerically investigate Whispering Gallery Modes (WGM) in a subwavelength microdisk resonator [1] embedded in an uniaxial anisotropic liquid crystal environment. It is shown that the WGMs have anticrossing behavior when modes of different radial mode order M or azimuthal order N approach each other spectrally.
Keywords: tet_topic_microdisk

Coherent control in hybrid metal-semiconductor nanostructures - Meier, Torsten; Reichelt, Matthias (DPG Spring meeting 2009)
Recently it has been shown experimentally that it is possible to coherently control nano-optical excitations by using sophisticated shaped laser pulses. In this work a similar technique is used to theoretically investigate a hybrid nanostructure which consists of a metal aperture and a quantum wire. It is shown that one can concentrate the optically excited electron density at an arbitrary position due to wave packet dynamics by chosing particular frequency components and phases of the chirped laser pulse. The optimization process is performed with a genetic algorithm which is linked to a 3D-FDTD solver.

Shaping the spatiotemporal dynamics of the electron density in a hybrid metal-semiconductor nanostructure - Reichelt, Matthias; Meier, Torsten (Optics Letters)
A one-dimensional semiconductor nanostructure is locally excited through a metal aperture. It is shown that the electron density can be coherently localized at desired spatial and temporal positions by using nontrivially shaped laser pulses. To obtain the optimized laser field, Bloch equations for a tight-binding model system are solved together with a genetic pulse-shaping algorithm. Full three-dimensional finite-difference time-domain (FDTD) simulations of the Maxwell–Bloch equations confirm the predicted coherent spatiotemporal control.

Generation of injection currents in (110)-oriented GaAs quantum wells: experimental observation and development of a microscopic theory - Bieler, M.; Pierz, K.; Siegner, U.; Dawson, P.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIII)
We have experimentally investigated injection currents generated by all-optical excitation of GaAs/AlGaAs quantum wells excited with 130 fs optical pulses. The currents have been detected via free-space THz experiments at room temperature. Our experiments prove that Coulomb effects strongly influence injection currents. This becomes most prominently visible when exciting light-hole exciton transitions. At this photon energy we observe a pronounced phase shift of the current transients which is due to oppositely oriented heavy-hole and light-hole type contributions. We are currently developing a microscopic theory based on a 14×14 k.p model in combination with the semiconductor Bloch equations to describe the observed features quantitatively. The combined theoretical and experimental approach will allow us to analyze the influence of the bandstructure and interaction effects on the injection current amplitude and current dynamics.
Keywords: tet_topic_qw

Microscopic theory of the linear and nonlinear Terahertz response of semiconductors - Meier, Torsten; Koch, S.W.; Kira, M.; Steiner, J.T.; Golde, D. (CLEO/Europe - EQEC 2009 - European Conference on Lasers and Electro-Optics and the European Quantum Electronics Conference)
The paper presents a theoretical analysis of the nonlinear THz response from the internal transitions of coherent and incoherent excitons based on the formulated microscopic THz theory. Moreover, the response of unexcited semiconductors to extremely intense THz fields is investigated .The intersubband transitions of optically excited quantum wells using linear THz spectroscopy is also studied. The computed differential transmission shows a characteristic Fano-like line shape of the intersubband resonance. The pure intersubband contribution is given by a simple Lorentzian. Applying the microscopic theory, the Fano features of the total response can be attributed to the phase-sensitive superposition of the intersubband transitions and the ponderomotive contribution. These results are in excellent agreement with recent experiments.

Ultrafast coherent photoelectron emission effects and their application for time-domain studies of current transport - Meier, Torsten; Koch, S.W.; Rohleder, M.; Gudde, J.; Hofer, U. (Conference on Lasers and Electro-Optics and 2009 Conference on Quantum electronics and Laser Science Conference)
By combining coherent control schemes and photoelectron spectroscopy it is possible to generate ultrafast current pulses at surfaces and in solids and to detect their decay directly in momentum space with femtosecond time resolution.

Determination of homogeneous and inhomogeneous broadenings of quantum-well excitons by 2DFTS: An experiment-theory comparison - Kuznetsova, Irina; Thomas, Peter; Meier, Torsten; Zhang, Tianhao; Cundiff, Steven T. (physica status solidi (c))
The recently developed two-dimensional Fourier-Transform-Spectroscopy (2DFTS) in the optical regime has been established as an elegant experiment, which has manifold of applications in the investigation of semiconductor nanostructures. Here we focus on the real and imaginary part 2DFT spectra. As predicted recently, using rephasing and non-rephasing modes, we are able to determine the homogeneous and inhomogeneous broadenings of coupled excitonic resonances even for weak disorder where photon-echo data are not useful. Computed real and imaginary parts of the 2DFTS for rephasing and non-rephasing modes are compared with experimental data of a GaAs quantum well. It is demonstrated, that phase sensitive data for the rephasing and non-rephasing modes are able to accurately provide the disorder induced broadening in a complex coupled system for each transition separately.

Microscopic analysis of high-harmonic generation in semiconductor nanostructures - Golde, Daniel; Meier, Torsten; Koch, Stephan W. (physica status solidi (c))
A microscopic analysis of the emitted radiation of a semiconductor nanostructure after excitation with an extremely intense ultrashort laser pulse is presented. It is shown that the extreme nonlinear optical response is not sufficiently described by pure interband transitions but one has to include intraband effects as well. Numerical solutions of extended Bloch equations that include the coupled inter- and intraband dynamics are presented. For large excitation intensities, the intraband effects strongly modify the polarization dynamics and lead to a strong enhancement of high-harmonic generation compared to pure interband dynamics.

Preface - Meier, Torsten; Michler, Peter (physica status solidi c)

Reiseprosa zwischen erlebter und erfundener Erfahrung von Wolfgang Büscher, Hape Kerkeling und Sigrid und Hamster Damm - Müller, Inez (Autobiographisches Schreiben in der deutschsprachigen Gegenwartsliteratur, Bd. 3: Entwicklungen, Kontexte, Grenzgänge.)

Photo-and spin current generation and dynamics in semiconductor nanostructures - Meier, Torsten; Duc, Huynh Thanh; Foerstner, Jens (DPG Spring meeting 2009)
The band structure and wave functions of GaAs quantum wells are computed via k.p band structure theory including anisotropy and spin splitting. Using these results, the process of generating photocurrents by optical excitation is analyzed. Depending on the symmetry of the material, the direction of the laser beam, and the polarization direction of the light field/s, one can coherently generate charge and/or spin photocurrents on ultrashort time scales. The direction, the strength, and the dynamics of these photocurrents are computed and discussed.